Laboratory Information Bulletin: Quantitation of Aflatoxin M1 in Bovine Milk by Liquid Chromatography with Fluorescence Detection. (27th November 2019) - Vega, Victor A; Young, Michelle; Todd, Sarah
Abstract: An extraction for aflatoxin M1 from bovine milk samples is described. The samples were extracted by adding 10 mL acetonitrile to 10 g of sample. The extract was salted out with sodium chloride and magnesium sulfate to separate the water and acetonitrile. The organic layer was dried down and reconstituted in water before being subjected to an immunoaffinity column for cleanup. Once the analyte was isolated, quantitation was obtained by LC with fluorescence detection. LC/fluorescence parameters were optimized with an Agilent Poroshell 120 C18 LC column resulting in a 4 min run time. To test the procedure's robustness, three different kinds of matrixes were fortified at three different levels each. Whole milk, reduced fat milk, and skim milk samples were fortified at approximately 0.25, 0.5, and 1.0 μg/kg. Recoveries from all samples ranged from 70 to 100%. Confirmation was accomplished by injecting the samples in an ion trap mass spectrometer. The method presented here entails an extraction step followed by an immunoaffinity column clean-up that leads to fast analysis time and consistent recoveries with an uncertainty measurement of 10.5% and method detection limit of less than 0.011 μg/kg.